IMPLEMENTASI PENDIDIKAN ANTIKORUPSI KE DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN (Studi Komparatif Pendidikan Anti-korupsi di Indonesia dan Singapura) - Rahma Halimatu Syadiah, - (2022)
The high number of corruption in Indonesia has brought Indonesia to the verge of worry and led the Indonesian people to a poor standard of living. Corrupt behavior seems to be entrenched in this country, a lot of behavior that is carried out is sometimes not realized that it is a corrupt culture, not to mention technological advances, especially social media, are even used as a place to show off wealth, which is contrary to the simplicity value of anti-corruption behavior. In this regard, the field of education certainly has a role to play in shaping an anti-corruption culture in the younger generation, one of which is through the implementation of anti-corruption education. Based on this, researchers are interested in conducting this research. This study aims to determine the implementation of anti-corruption education. Research with the theme of anti-corruption education is qualitative research using a descriptive comparative method. This research was conducted through literature studies, interviews and documentation. The issue of corruption is very important to discuss, especially discussing its eradication, one of which is by preventing corruption through education, 1) Each country has a different strategy in implementing anti-corruption education as well as Indonesia and Singapore, in its implementation 2) Each party play an important role in the realization of anti-corruption education, including learning Pancasila and citizenship education., 3) The use of the right strategy will help the process of implementing anti-corruption education through Pancasila and civic education., 4) Its implementation in the world of education must always have factors that hinder its implementation , but of course behind these obstacles there are things that can be a solution in its implementation. Keyword: Anti Corruption Education, Pancasila and Citizenship Education, Anti Corruption Education in Indonesia, Anticorruption Education in Singapore